(untitled) (Torani Journal of Fisheries and Marine Science, 2017)
Bone Strait and Flores sea are Indonesian waters which has a high fish resources, especially Katsuwonus pelagicus. Those waters are also affected by climate change. Aims of study were to examined distribution map of Katsuwonus fish based on environemental condition at Bone Strait and Flores Sea. Study was conducted for four months (May – August 2015). Environment parameters (Sea level temperature, Chl a, salnity and pH) was measured in situ at fishing area and fish weight data was measured through measuring fish that caught from pole and line fishermen. Results showed that Katsuwonus from Bone Strait (1 – 2 kg and 3.5 – 5 kg) tended to distribute at temperature, Chl a, salinity and pH account for 29.3oC – 30oC, 0.8 – 1.5 mg/m3 and 28 – 30 o/oo, 7.95 – 8.37 respectively. meanwhile fish with 2 – 2.5 kg was distributed at 30oC – 30.3oC, 0.6 – 0.7 mg/m3, 28 – 29 o/oo and 8.32 – 8.5 for temperature, Chl a, salinity and pH, respectively. At Flores Sea, Katsuwonus with 1.2 – 1.5 kg tended to distribut at 29.5oC – 30oC, 0.12 – 0.16 mg/m3, 28 – 30 o/oo and 7.95 – 8.57 for temperature, chl a, salinity and pH, respectively. Fish with weight 1.5 – 2.2 kg was spread at 28.5oC – 29oC for temperature, 0.1 – 0.13 mg/m3 chl a, 28 – 30o/oo for salinity and 8.38 – 8.5 for pH. Keywords : Distribution map, Katsuwonus fish, environmental factor, Bone Strait and Flores Sea.